Analysis of disclosure of environmental indicators of the biggest companies in the pulp and paper sector - Mady, Caio Assis; Mady, Fábio Assis; Rodrigues, Felipe Nascimento Caivano; Souza, Maria Tereza de Saraiva; Galvão, Reny Aparecida (Revista de Administração da UFSM, 2018)
This study aims to compare the evidence level of environmental indicators that follow the GRI guidelines, related to the three leading companies in Brazilian pulp and paper industry, Suzano, Klabin and Fibria, in 2012. For achieving this goal, annual sustainability reports and websites of the companies studied were analyzed. The companies reported mainly those aspects related to materials, water, biodiversity and others, while products and services, compliance and energy were less emphasized. The results show that the three companies presented a low evidence level, with missing or incomplete indicators. Finally, despite the reports presented and classified as A+ and B+, it is possible to conclude that the companies did not include key indicators and presented unorganized information and lack of standardization.